2022
DOI: 10.1016/j.microc.2021.107101
|View full text |Cite
|
Sign up to set email alerts
|

Novel environment friendly TLC-densitometric method for the determination of anti-coronavirus drugs “Remdesivir and Favipiravir”: Green assessment with application to pharmaceutical formulations and human plasma

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Phases A & B are eluted in a gradient mode. Published HTPLC ( Noureldeen et al, 2022 ) Ethyl acetate: methanol: ammonia (8:2:0.2) 1 mL/sample (4 green, 10 yellow, 1 red) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phases A & B are eluted in a gradient mode. Published HTPLC ( Noureldeen et al, 2022 ) Ethyl acetate: methanol: ammonia (8:2:0.2) 1 mL/sample (4 green, 10 yellow, 1 red) …”
Section: Resultsmentioning
confidence: 99%
“…Finally, a comprehensive appraisal of the method's eco-friendliness was carried out using Analytical Eco-scale (AES) ( Gałuszka et al, 2012 ), Green Analytical Procedure Index (GAPI) ( Płotka-Wasylka, 2018 ) and Analytical Greenness (AGREE) ( Pena-Pereira et al, 2020 ) metrics. Besides, a thorough comparison of the method's greenness with other previously published stability indicating HPLC procedures ( Ibrahim et al, 2021 ; Hamdy et al, 2021 ; Ramakrishna Reddy et al, 2021 ; Surabhi and Jaina, 2021 ) and the only reported HPTLC direct determination of RMD ( Noureldeen et al, 2022 ) was also illustrated using the more inclusive GAPI and AGREE metrics.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, method No. 16 [20] is considered the worst environmentally depending on ESA (80), GAPI (5 green sections), and AGREE tool (0.46).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, REM was quantitatively determined with its metabolite in human serum [12] and in rat serum [13] . During the establishment of the research, the published researches related to the drug under study followed, as many research papers were just published, and then they were integrated into our environmental study [14] , [15] , [16] , [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%